2016
DOI: 10.3390/genes7010003
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of Field Trial Sites with Genetically Modified Oilseed Rape (Brassica napus L.) in Saxony-Anhalt, Germany. Fifteen Years Persistence to Date but No Spatial Dispersion

Abstract: Oilseed rape is known to persist in arable fields because of its ability to develop secondary seed dormancy in certain agronomic and environmental conditions. If conditions change, rapeseeds are able to germinate up to 10 years later to build volunteers in ensuing crops. Extrapolations of experimental data acted on the assumption of persistence periods for more than 20 years after last harvest of rapeseed. Genetically-modified oilseed rape—cultivated widely in Northern America since 1996—is assumed not to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Oilseed rape (Brassica napus AACC) is an annual allotetraploid species (2n = 38, genome constitution AACC), which has probably evolved through hybridisation and polyploidisation between the two diploid species Brassica rapa (2n = 20, AA) and Brassica oleracea (2n = 18, CC). Oilseed rape seeds have the ability to survive in soils for more than 10 years (Hails et al, 1997;Begg et al, 2006;Lutman et al, 2004;Lutman et al, 2005;Lutman et al, 2008;Mess ean et al, 2007;D'Hertefeldt et al, 2008;Gruber et al, 2008;Beckie and Warwick, 2010;Peltonen-Sainio et al, 2014;Belter, 2016) and demographic studies and surveys have shown the ability of oilseed rape (B. napus) seed to establish self-perpetuating populations outside agricultural areas, mainly in semi-natural and ruderal habitats in different countries (e.g. Crawley et al, 1993;Pascher et al, 2010Pascher et al, , 2017Devos et al, 2012;Bauer-Panskus et al, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Bailleul et al, 2016;Busi and Powles, 2016;Franzaring et al, 2016;Nishizawa et al, 2016).…”
Section: Persistence and Invasiveness Of The Gm Plantmentioning
confidence: 99%
“…Oilseed rape (Brassica napus AACC) is an annual allotetraploid species (2n = 38, genome constitution AACC), which has probably evolved through hybridisation and polyploidisation between the two diploid species Brassica rapa (2n = 20, AA) and Brassica oleracea (2n = 18, CC). Oilseed rape seeds have the ability to survive in soils for more than 10 years (Hails et al, 1997;Begg et al, 2006;Lutman et al, 2004;Lutman et al, 2005;Lutman et al, 2008;Mess ean et al, 2007;D'Hertefeldt et al, 2008;Gruber et al, 2008;Beckie and Warwick, 2010;Peltonen-Sainio et al, 2014;Belter, 2016) and demographic studies and surveys have shown the ability of oilseed rape (B. napus) seed to establish self-perpetuating populations outside agricultural areas, mainly in semi-natural and ruderal habitats in different countries (e.g. Crawley et al, 1993;Pascher et al, 2010Pascher et al, , 2017Devos et al, 2012;Bauer-Panskus et al, 2013;Hecht et al, 2014;Schulze et al, 2014;Katsuta et al, 2015;Bailleul et al, 2016;Busi and Powles, 2016;Franzaring et al, 2016;Nishizawa et al, 2016).…”
Section: Persistence and Invasiveness Of The Gm Plantmentioning
confidence: 99%
“…Even though spread of GM plants is often hypothesized to occur through cross-pollination with compatible non-GM crop plants or wild species, the literature search reported only a limited number of cases demonstrating transfer of transgenic pollen, e.g., for maize in South Africa (Viljoen and Chetty, 2011) or oilseed rape in Japan (Tsuda et al., 2012). In summary, even though it is possible that imported GM seed material can be inadvertently introduced to the EU environment and, in some cases, depending on species fitness, can establish persisting plant populations, e.g., oilseed rape, the available evidence suggests that probability of gene transfer from persisting population to crop plants via hybridization is very low (Belter, 2016; Devos et al., 2012).…”
Section: Main Textmentioning
confidence: 99%
“…Oilseed rape readily produces volunteers and feral plants, due to its high seed production, high seed losses during harvest and transport, and its secondary dormancy [97]. HR oilseed rape plants have been found up to 15 years after experimental releases, despite regular control of the fields for volunteers [98, 99]. The recently reported incidence of oilseed rape seed contamination by the non-approved OXY-235 variety (resistant to oxynil herbicides) in the EU might be traced back to field trials in France in the nineties [100], indicating that volunteers may emerge even after almost 20 years.…”
Section: Reviewmentioning
confidence: 99%